A facile route to graphite-tungsten nitride and graphite-molybdenum nitride nanocomposites and their ORR performances. Issue 14 (1st November 2016) - Pan, Xiaolong; Song, Xinhang; Lin, Sen; Bi, Ke; Hao, Yanan; Du, Yinxiao; Liu, Jun; Fan, Dongyu; Wang, Yonggang; Lei, Ming
Abstract: The use of various advanced functional ceramics has been widely implemented in various fields, yet still limited in energy-based fields, such as regenerative fuel cells. Here, a two graphite covered metal nitride nanoparticle ceramic (graphite-tungsten nitride and graphite-molybdenum nitride nanocomposites) was synthesized via a one-step solid phase method. TEM photographs show 10 nm ceramic particles and a clear carbon coating layer. Such a novel carbon coating layer was further confirmed to be graphite via Raman spectroscopy and X-ray photoelectron spectroscopy (XPS). Raman spectra of as-prepared samples displayed unique structural defects of the graphite layer, giving it excellent capability of oxygen molecule capture. The oxygen reduction reaction (ORR) polarization curves obtained from linear sweep voltammetry (LSV) via rotating disk electrode (RED) showed ORR activity (via a two-electron pathway) of both G-Mo2 N and G-WN. Subsequently, the durability of G-Mo2 N and G-WN were tested via chronoamperometry, in which both samples retained more than 80% of their initial current after 10, 000 s, allowing for the material to overcome the shortcomings of traditional ceramic materials including low conductivity, inferior catalytic activity and unsatisfactory durability.